Rancang Bangun Aplikasi Tracking Kendaraan Berbasis Android - Salamun Salamun; Jon Fery Sitepu; Ira Puspita Sari (Politeknik Caltex Riau, 2023)
Centered light and heavy equipment rental services are services that have a high risk of loss. Most car tracking systems are still web-based, making it difficult to track and update vehicle rental unit information. In this study, the authors carried out several stages, namely interviews with related parties and following the vehicle tracking process through an ongoing system. Then proceed with an analysis of the needs of the ongoing system development. The programming language used in the development of this system is Android Studio, along with Google Maps and the use of GPS that is needed, which uses the MySql database. The development of a vehicle tracking application will maximize the existing GPS on the vehicle and the functions of Google Maps. With the Android-based vehicle tracking application, it is hoped that it will make it easier for employees and consumers to carry out the process of searching for data and information, as well as tracking units that run in a short time.